Two Tales of Piracy. (10th March 2022) - Blayney, Peter W M
Abstract: While book-piracy is often thought of as an Elizabethan problem, the organized infringement of lucrative copyrights in fact began a few decades earlier, in the reign of Mary Tudor. In this paper the known details are presented of what are probably the two best documented cases from that reign. The first was the repeated commissioning and importation of editions of Lily's Grammar from Geneva (some of them falsely dated). The second was the reprinting of a collection of sermons whose authorized printer had secured a patent to protect it. In the first case the patentee's attempts to obtain satisfaction in Chancery were unsuccessful; in the second the author's interests fared rather better in Star Chamber, and may thus have established a precedent for the prosecution of Elizabethan pirates.